2020
DOI: 10.1002/ajb2.1443
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships and polyploid origins in the Lippia alba complex

Abstract: Premise Plant genomes vary in size and complexity due in part to polyploidization. Latitudinal analyses of polyploidy are biased toward floras of temperate regions, with much less research done in the tropics. Lippia alba has been described as a tropical polyploid complex with diploid, triploid, tetraploid, and hexaploid accessions. However, no data regarding relationships among the ploidal levels and their origins have been reported. Our goals are to clarify the relationships among accessions of Lippia alba a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…There is natural polyploidy within the species, a mechanism of plant speciation that results in morphological plasticity and the presence of several chemotypes (Reis et al, 2014). Lopes et al (2020) studied genetic relationships and polyploid origins in the L. alba complex, and they found that there is an association between morphological characters and ploidal level but the patterns of genetic and chemical variation are not related to geographical distribution. Biotypes found in the subtropical regions of America (both in the north and in the south) are characterized by pendulous branches, and it is assumed that this feature is a response to periods of low temperatures.…”
Section: Resumen "Química De Los Aceites Esenciales Del Arbustomentioning
confidence: 99%
“…There is natural polyploidy within the species, a mechanism of plant speciation that results in morphological plasticity and the presence of several chemotypes (Reis et al, 2014). Lopes et al (2020) studied genetic relationships and polyploid origins in the L. alba complex, and they found that there is an association between morphological characters and ploidal level but the patterns of genetic and chemical variation are not related to geographical distribution. Biotypes found in the subtropical regions of America (both in the north and in the south) are characterized by pendulous branches, and it is assumed that this feature is a response to periods of low temperatures.…”
Section: Resumen "Química De Los Aceites Esenciales Del Arbustomentioning
confidence: 99%